Onycocaris maui sp. nov., a new pontoniine sponge associate (Crustacea: Decapoda: Palaemonidae) from the Hawai’ian Islands - Bruce, A. J. (Zootaxa, 2013)
A new species of pontoniine shrimp, Onycocaris maui sp. nov., from Maui Island, Hawai’i, is described and illustrated. A heterosexual pair were found in an intertidal Haliclona sponge. A member of the O. quadratophthalma species group, its relationships are discussed and a key provided for their identification.